Medication for addiction treatment and acute care utilization in HIV-positive adults with substance use disorders. Issue 9 (1st September 2020) - Thakarar, K.; Walley, A. Y.; Heeren, T. C.; Winter, M. R.; Ventura, A. S.; Sullivan, M.; Drainoni, M.; Saitz, R.
ABSTRACT: Medication for addiction treatment (MAT) could reduce acute care utilization in HIV-positive individuals with substance use disorders. The study objective was to determine if HIV-positive people with substance use disorders treated with MAT report less acute care utilization than those not receiving MAT. We assessed the association between MAT and acute care utilization among HIV-positive individuals with alcohol or opioid use disorder. Acute care utilization 6 months later was defined as any past 3-month self-reported (1) emergency department (ED) visit and (2) hospitalization. Of 153 participants, 88% had alcohol use disorder, 41% had opioid use disorder, and 48 (31%) were treated with MAT. Fifty-five (36%) participants had an ED visit and 38 (25%) participants had a hospitalization. MAT was not associated with an ED visit (AOR 1.12, 95% CI 0.46–2.75) or hospitalization (AOR 1.09, 95% CI 0.39–3.04). MAT was not associated with acute care utilization. These results highlight the need to increase MAT prescribing in HIV-positive individuals with substance use disorders, and to address the many factors that influence acute care utilization.